Biochemical responses of juvenile and adult Japanese quails to cyanobacterial biomass - Pecková, Lucie; Banďouchová, Hana; Hilscherová, Klára; Damková, Veronika; Sedláčková, Jana; Vitula, František; Pašková, Veronika; Pohanka, Miroslav; Kohoutek, Jiří; Pikula, Jiří (Neuro-endocrinology letters, 2009)
OBJECTIVES: The aim of the present study was to evaluate differences between juvenile and adult Japanese quails in responses to the exposure to cyanobacterial biomass in the diet. DESIGN: The OECD 205 Guideline on Avian Dietary Toxicity Test (1984) was employed in the experiment. A total of 75 freshly hatched chicks and 30 adults were exposed to cyanobacterial biomass for 15 days and blood sampled daily and on days 5, 10 and 15, respectively. Japanese quail chicks and adults received the same daily dose of approximately 224.4 ng microcystins per gram of body weight. Biochemical responses were compared against controls. RESULTS: No Japanese quail chicks and adults died during the acute 15-day-cyanobacterial-biomass exposure. Biochemical responses to the biomass in diet were first observed from day 5 post exposure to cyanobacterial biomass both in chicks and adults and there were age-related differences in the parameters changed. The responses of adult birds included an increase in lactate dehydrogenase, a drop in glucose and the total antioxidant capacity as well as a 15 to 20 % inhibition of acetylcholinesterase activity. Japanese quail chicks exposed to cyanobacterial biomass for the first 15 days after hatching reacted by having hypoproteinaemia, increased concentrations of triglycerides, uric acid and the total antioxidant capacity and a drop in high-density lipoprotein cholesterol in the blood. CONCLUSIONS: Chicks were not found to be more susceptible to the effects of biomass exposure. It seems that, due to their physiological preparation for the oxidative stress associated with hatching, Japanese quail chicks were even better able to cope with the cyanobacterial-biomass-induced oxidative stress than adults.
Keywords: Animals; náhodné rozdělení; Uric Acid; fyziologický stres; kyselina močová; dieta; Hypoproteinemia; biomasa; L-Lactate Dehydrogenase; zvířata; Diet; Stress, Physiological; Aging; Triglycerides; Random Allocation; triglyceridy; acetylcholinesterasa; stárnutí; Cholesterol, HDL; časové faktory; Time Factors; Acetylcholinesterase; Male; hypoproteinemie; L-laktátdehydrogenasa; Coturnix; krevní glukóza; antioxidancia; Blood Glucose; Biomass; HDL-cholesterol; Cyanobacteria; mužské pohlaví; sinice; Antioxidants